Sejarah Perkembangan Dinasti Mughal dan Penguasa Muslim di Tanah India Tahun 1525-1857 - Aidil Fitrah; Nur Sarimah; Elga Febriani; Dinda Dinda; Koryati Koryati; Novita Fitriani; Dwi Noviani (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This article discusses the Mughal Dynasty which ruled India from 1526 to 1857. the causes of the decline and fall of the kingdom, as well as the high heritage of Islamic culture in India during the Mughal Dynasty period. This research illustrates the importance of the Mughal Dynasty in Indian history and its impact on cultural development and social life. Data was collected through historical study and analysis of related documents. The findings of this research provide a better insight into the heyday and fall of the Mughal Dynasty, as well as its influence in shaping India's cultural identity.